PELATIHAN TENAGA KERJA - Mahmud; Didik Hariono; Putri Puspita Sari (Dar El-Falah, 2023)
Steps in identifying training needs: organizational analysis, consultation withrelated parties, job analysis, identification of individual needs, prioritizationof needs, development of training plans, measurement of success,implementation and evaluation. Steps that need to be considered in designinga successful HR training program: determine training objectives, identifytraining participants, select methods and curriculum, training activities,select instructors, scheduling and logistics, training evaluation, programrevision, program implementation, ongoing monitoring and evaluation Stepsthat can help evaluate the effectiveness of HR training: determine evaluationobjectives, identify success criteria, data collection before training, formativeevaluation during training, post-training performance measurement,feedback from participants, measurement of participant satisfaction, data analysis, impact evaluation on the organization, identify necessaryimprovements, continuous improvement.The main role of continuouslearning in the organization: improving individual and team performance,continuous innovation and improvement, adapting to change, increasingemployee retention, increasing customer satisfaction, increasingorganizational competitiveness, improving organizational image.